Bone microarchitecture, bone mineral density and bone turnover in association with glycemia and insulin action in women with prior gestational diabetes. (24th November 2021) - Kubihal, Suraj; Gupta, Yashdeep; Goyal, Alpesh; Kalaivani, Mani; Tandon, Nikhil
Abstract: Objective: The aim of this cross‐sectional study was to comprehensively assess bone health in women with prior gestational diabetes mellitus, including bone microarchitecture (TBS), bone mineral density (BMD, DXA) and bone turnover (osteocalcin). Design, Patients and Measurements: Study participants underwent a detailed anthropometric, biochemical and hormone assessment, including insulin and osteocalcin measurement. BMD was measured at lumbar spine, femur neck and total hip using DXA and TBS derived from lumbar spine DXA images using TBS iNsight software. Results: A total of 240 women (mean age: 33.3 ± 5.0 years; median postpartum duration: 34 [interquartile range 13.0–54.5] months were evaluated. At the current visit, 115 (47.9%) and 36 (15%) women had prediabetes and diabetes, respectively. Women with dysglycemia (diabetes/prediabetes) had a higher BMD at all three sites, compared to those with normoglycemia; however, the difference was not statistically significant. Women with dysglycemia had a significantly lower TBS (1.32 ± 0.09 vs. 1.35 ± 0.09; p = .038). In the fully adjusted model, the odds ratio for association between diabetes and low TBS was 2.92 (95% confidence interval: 1.20, 7.08; p = .018). Women with dysglycemia had significantly lower serum osteocalcin levels (18.6 ± 8.5 ng/ml vs. 21.5 ± 9.7 ng/ml; p = .018). HOMA‐IR ( r = −.285, p < .001) was negatively correlated, while Matsuda index ( r = .274, p < .001) and disposition index ( r = .159, p = .016) were positively correlated with serum osteocalcin levels. Conclusions: Bone health is affected early in the natural history of diabetes and is associated with an overall low bone turnover state.